Agriculture Crop Residue Burning and Its Consequences on Respiration Health of School-Going Children. (September 2019) - Gupta, Sachin
Crop waste burning in open fields is a matter of concern in relation to health-related complications in humans of all age groups, especially children. An epidemiological study was been done on school children to estimate the decline in their physiological parameters due to crop residue burning activity. A total of 150 children were inspected for 3 years (2013-2016) at 3 different sites in India. During sampling periods, spirometric tests, ambient particulate matter having size ≥10 µg −3 and ≥2.5 µg −3, and other covariates were measured twice in a fortnight. After adjustment of data in multivariate mixed-effect model, prediction and statistical analyses were done. From results obtained, it has been observed that season wise, the level of fine particulate matter (PM10 and PM2.5 ) was higher in rice crop residue burning seasons than in wheat crop residue burning seasons by 87% to 123% than permitted monthly limits. As per dose-response relationship, maximum degradation was observed in forced vital capacity (−7.62%) and peak expiratory flow (−6.23%) parameters from their baseline values due to burning activities. Prediction equations have been purposed to observe the future trends in physiological parameters of children. Based on Tiffeneau index, an unrecoverable effect was seen in lung parameters. Trends were alarming and may cause serious complications in early age of humans.